Placement technique of extended spreader grafts - (:unkn) unknown (My University, 2011)
OBJECTIVES: This study aims to show the placement of extended spreader grafts in reductive septorhinoplasty operations to support the nasal bony vault as well as the middle cartilaginous structures. PATIENTS AND METHODS: Thirty-eight patients (16 males, 22 females; mean age 26.4 years; range 18 to 55 years) who underwent septorhinoplasty under general anesthesia via open approach between January 2008 and December 2010 were included in this study. Two separate cartilage grafts were placed end-to-end and secured to the septum on both sides after removing the cartilage and bony hump. These grafts not only transverse the full length of the middle one-third of the nose, also run approximately 1 cm under the nasal bones cephalically and the anterior septal angle caudally on both sides. The obtained data were evaluated retrospectively. Patients were followed up postoperatively for 7 to 24 months with a mean follow-up of 14 months. RESULTS: There was no significant bony vault collapse or irregularity, inverted-V deformity or middle-vault narrowing observed during the postoperative period. All of the patients were satisfied with the cosmetic and functional results. CONCLUSION: We think that extended spreader grafts are more beneficial not only in reconstructing the middle one-third of the nose but also in supporting the collapsed and/or distrupted nasal bony vault in reductive septorhinoplasty.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Adolescent; Male; Retrospective Studies; Young Adult; Surgical Flaps; Nose; Cartilage; Rhinoplasty; Nasal Bone